2011
DOI: 10.1038/oby.2011.14
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Whey Protein Decreases Food Intake and Body Fat in Rats

Abstract: We investigated the effects of dietary whey protein on food intake, body fat, and body weight gain in rats. Adult (11–12 week) male Sprague–Dawley rats were divided into three dietary treatment groups for a 10-week study: control. Whey protein (HP-W), or high-protein content control (HP-S). Albumin was used as the basic protein source for all three diets. HP-W and HP-S diets contained an additional 24% (wt/wt) whey or isoflavone-free soy protein, respectively. Food intake, body weight, body fat, respiratory qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 34 publications
4
44
3
4
Order By: Relevance
“…The suggestion that whey proteins induce satiety has been further confirmed in mice by showing that whey protein isolate providing 30% energy increased intermeal interval (satiety) compared to soy protein during the 7 day period of the study [7]. Similar findings have been reported from a long term study lasting 10 weeks [8]. These data are consistent with the findings from human studies that whey proteins reduce food intake by inducing satiety in the lean state.…”
Section: Food (Energy) Intakesupporting
confidence: 81%
See 2 more Smart Citations
“…The suggestion that whey proteins induce satiety has been further confirmed in mice by showing that whey protein isolate providing 30% energy increased intermeal interval (satiety) compared to soy protein during the 7 day period of the study [7]. Similar findings have been reported from a long term study lasting 10 weeks [8]. These data are consistent with the findings from human studies that whey proteins reduce food intake by inducing satiety in the lean state.…”
Section: Food (Energy) Intakesupporting
confidence: 81%
“…In the studies mentioned above, except for the latter, the observed effects of whey protein on lipid metabolism were shown relative to casein. Interestingly, in contrast, soy proteins at 24% (wt/wt) in the diet of rats had a similar effect on body weight and abdominal fat as whey proteins [8]. This data could be interpreted to suggest that whey protein effects on lipid metabolism are detectable only when casein is used as the control protein, or that the lack of an effect on lipid metabolism in comparison to soy might be due to the fact that the above study assessed dietary protein effects on lean rats as oppose to obese rodents, which are known to have a higher body weight and body fat content and thus, are likely to be more susceptible to whey protein effects on lipid metabolism.…”
Section: Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies in human subjects have reported no differences in the PYY response to a whey v. casein protein meal (105) or whey v. both pea protein hydrolysate and a combined casein/whey milk protein (80 % casein, 20 % whey) (106) . Further, a 10-week feeding study in rats found no differences in plasma PYY levels between whey and soya protein diets (107) . Conversely, PYY mRNA was down-regulated in rats following a lifetime of a high-whey diet v. high-casein or high-soya diets (108) .…”
Section: Impact Of Macronutrients On Peptide Yymentioning
confidence: 99%
“…Dentre as propriedades funcionais desses peptídios, pode-se citar as ações antihipertensiva (MORAIS et al, 2014;, hipocolesterolêmica, imunomoduladora (SINHA et al, 2007), antioxidante (SINHA et al, 2007;SILVESTRE et al, 2013), inibidora do apetite e redutora de gordura corporal (ZHOU et al, 2011;SOUSA et al, 2012).…”
Section: Introductionunclassified